MINERAÇÃO, TRABALHO E CONFLITOS AMAZÔNICOS NO SUDESTE DO PARÁ - Celia Regina Congilio (Universidade Federal do Maranhão, 2014)
The article analyzes the contemporary processes of Amazonian occupation, having as reference the mining activity in southeast Pará – specifically the concentrated in the vicinity of the city of Marabá - and the conflicts generated by the predatory way of this production chain (mining - coal – steel mill - iron and steel) which expels peasants and riparian which were previously produced and reproduced their existences. Notes that these actions produce chaotic urbanization, (in) civilizational actions which idealized notion of progress brings the real meaning of capital expansion, death and devastation.